2020
DOI: 10.1039/c9nj05405g
|View full text |Cite
|
Sign up to set email alerts
|

The immobilizing polysulfide mechanism of cadmium-doping carbon aerogels via a microtemplate for high performance Li–S batteries

Abstract: We develop a novel microtemplate strategy to prepare unique carbon aerogels. The designed cathode materials present excellent electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…This explains why the TiO 2 -Li 2 S 4 diffusion barrier is high. As a result, we conclude that the lithiumions diffusion barrier on the TMOs surface is higher than that (111), [77] TiO 2 (110), [78] V 2 O 3 (110), [79] Cr 2 O 3 (104), [57] MnO 2 (211), [80] Fe 3 O 4 (220), [50] CoO (002), [61] ZnO (101), [52] Nb 2 O 5 (110), [65] MoO 2 (-111), [81] CdO (200), [69] In 2 O 3 (110), [71] W 18 O 49 (010), [74] and CeO 2 (111) [75] surface. d) Comparisons of binding energies between Li 2 S n (n = 1, 2, 4, 6, and 8) /S 8 and common TMOs (All comparisons are used for objective evaluation only).…”
Section: The Lithium-ion Diffusion Characteristicsmentioning
confidence: 99%
“…This explains why the TiO 2 -Li 2 S 4 diffusion barrier is high. As a result, we conclude that the lithiumions diffusion barrier on the TMOs surface is higher than that (111), [77] TiO 2 (110), [78] V 2 O 3 (110), [79] Cr 2 O 3 (104), [57] MnO 2 (211), [80] Fe 3 O 4 (220), [50] CoO (002), [61] ZnO (101), [52] Nb 2 O 5 (110), [65] MoO 2 (-111), [81] CdO (200), [69] In 2 O 3 (110), [71] W 18 O 49 (010), [74] and CeO 2 (111) [75] surface. d) Comparisons of binding energies between Li 2 S n (n = 1, 2, 4, 6, and 8) /S 8 and common TMOs (All comparisons are used for objective evaluation only).…”
Section: The Lithium-ion Diffusion Characteristicsmentioning
confidence: 99%
“…As a result, a CA/S/Sm electrode delivered an initial discharge capacity of 1,212 mAh g −1 at 0.5 C and a reversible capacity of 866 mAh g −1 after 300 cycles. Recently, Ding et al also reported a cadmium-doping carbon aerogel for highperformance Li-S batteries (Ma et al, 2020). And the relative DFT calculation and experiment results have proved that Cd doping played a vital role in effectively entrapping the polysulfides.…”
Section: Other Transition Metal Atom-decorated Carbon Materialsmentioning
confidence: 99%
“…In addition to the above two categories of metal atom-decorated carbon materials, in recent years, some other transition metal atom-decorated carbon materials as the sulfur host have been (Zhou et al, 2019) used to simultaneously accelerate the LiPS redox reaction and chemically trap the LiPS adsorption (Sheng et al, 2019;Fan et al, 2020;Ma et al, 2020). For example, Cui's group first used the DFT calculation to calculate the decomposition barrier of various metal atoms (Fe, Mn, Ru, Zn, Co, Cu, V, and Ag) on N-doped graphene materials and discovered that vanadium single atoms on N-doped graphene (SAV@NG) showed the smallest decomposition barrier (1.10 eV) as shown in Figure 4A (Zhou et al, 2019).…”
Section: Other Transition Metal Atom-decorated Carbon Materialsmentioning
confidence: 99%
“…[1][2][3][4][5] Sulfur, an active cathode material, is highly abundant in the earth's crust and hence is eco-friendly and inexpensive. 6 However, some serious drawbacks caused by security issues and its sluggish conversion efficiency still impede its practical application. 7 Sulfur has intrinsically low electrical conductivity, gradually forms lithium polysulfides as intermediates (Li 2 S x , x = 2-8), and finally generates insoluble Li 2 S.…”
Section: Introductionmentioning
confidence: 99%